New developments in the 1-aza-Diels-Alder reaction : versatile routes to pyridines - Hurst, Timothy E. (2008)
In Chapter one a review of the l-aza-Diels-Alder reaction is presented. The hetero Diels-Alder reaction of l-aza-l,3-butadienes with both alkene and alkyne dienophiles has been shown to be an efficient and versatile method for the preparation of a large range of nitrogen-containing six-membered heterocycles. The use of electron-rich 1- azadienes in the normal electron-demand Diels-Alder reaction is primarily examined, followed by a brief look at the synthetic applications of the inverse electron-demand process. In Chapter two the intermolecular hetero-Diels-Alder cyc1oadditions of 3-siloxy-1aza-1,3-butadienes with electron-deficient dienophiles is presented as an efficient route to tri- and tetra-substituted pyridine core of the thiopeptide antibiotic nosiheptide. A series of alpha, beta-unsaturated oximes and hydrazones were prepared and subsequently shown to participate readily in the hetero-Diels-Alder reaction with dimethyl acetylenedicarboxylate. In Chapter three, the intramolecular Diels-Alder reaction is presented as a versatile method for the preparation of chromeno[ c ]pyridines. First a series of model systems was prepared and shown to undergo thermally induced intramolecular cyc1oaddition. This methodology was then utilised in the rapid preparation of the penta-substituted pyridine core of the anti tumour antibiotic streptonigrin. Chapter four contains experimental procedures for all of the work detailed above.